Gender gap in pharmacological reperfusion and outcomes of ST-elevation acute myocardial infarction: Paraguayan cohort 2019–2023. - Ortellado, José; González, Graciela; Gaona Figueredo, Gabriel; Rolón Ruiz Diaz, Angel Ricardo; Ferreira Gaona, Marta (Medicina Clínica y Social, 2025)
Introduction: ST-elevation acute myocardial infarction (STEMI) is one of the leading causes of cardiovascular morbidity and mortality. Early reperfusion, mainly through fibrinolysis in developing countries, is essential to reduce complications and mortality. However, multiple international registries have documented gender inequities in access to reperfusion therapies, with greater delays and worse outcomes in women. In Paraguay, where fibrinolysis remains the most widely used strategy under the IAM Code, there had been no national analysis to assess these differences. Objective: To assess the gender gap in pharmacological reperfusion and in-hospital outcomes in patients with STEMI in Paraguay between 2019 and 2023. Methodology: Observational, retrospective, multicenter study based on the national registry of the IAM Code. Consecutive patients with acute coronary syndrome were included. Clinical characteristics, risk factors, reperfusion strategies, critical times, and in-hospital outcomes were analyzed using ?² and Mann–Whitney U tests, with significance set at p<0.05. Results: A total of 1,831 patients were included. Women were older (65.6 ± 12.4 vs. 60.3 ± 11.4 years; p<0.001) and had more hypertension, diabetes, and obesity, while smoking and alcohol consumption were more common in men. Fibrinolysis was performed in 64.1% of patients, less frequently in women than in men (61.1% vs. 66.2%; p=0.048). Critical times were longer in women: symptom-to-door (310 vs. 280 min), door-to-needle (50 vs. 40 min), and total ischemia (370 vs. 340 min; p<0.001). In-hospital mortality was higher in women (12.4% vs. 7.8%; p<0.001), as was heart failure (15.2% vs. 10.5%; p=0.01), while no significant sex differences were found in ventricular arrhythmias, stroke, or major bleeding. Conclusion: Women with STEMI in Paraguay have lower access to fibrinolysis, longer treatment delays, and worse in-hospital outcomes, confirming persistent gender inequities that require targeted health strategies.